Thyroid-Related Hormones Changes Predict Changes in Anthropometric Measures and Incidence of Obesity in Chinese Euthyroid Persons - Deng, Ling; Zheng, Xiaoxia; Shuai, Ping; Yu, Xijie (Hormone and Metabolic Research, 2023)
The purpose of this study was to investigate the correlation of thyroid-related hormones changes within the reference range with the changes in anthropometric measures and incidence of obesity. The study included 4850 subjects with normal thyroid-related hormones at baseline and at follow-up. We evaluated the relationship of changes in thyroid-related biomarkers with anthropometric measures changes and incidence of obesity. In euthyroid persons, changes in serum thyroid stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) concentrations and FT3/FT4 ratio were independent predictors of changes in body mass index (BMI) and waist circumference (WC) in men, changes in serum FT3 and FT4 concentrations and FT3/FT4 ratio were independent predictors of changes in BMI and WC in women. Every single unit increment in ΔFT3/FT4 was accompanied by a 7.144 and 7.572 times risk of having obesity in men and women, respectively. Every single unit decrement in ΔFT4 was accompanied by a 21.0% and 26.9% lower risk of having obesity in men and women, respectively. In conclusion, in euthyroid individuals, changes in thyroid-related hormones were associated with anthropometric measures changes and incidence of obesity.
Keywords: thyroid-related hormone; anthropometric measure; obesity; euthyroid person